Woulda, coulda, shoulda: the Evaluation and the Impact of the Alternative Outcome - Gu, Ruolei (2011)
The alternative outcome refers to the outcome of the unselected option in decision-making tasks, which has significant influence on the chosen outcome evaluation. Most paradigms have presented the alternative outcome either after or simultaneous with the chosen outcome, which complicates the observation on the brain activity associated with the alternative outcome. To circumvent this perceived shortcoming, we modified the classic paradigm designed by Yeung & Sanfey (2004) such that the alternative outcome was presented before the chosen outcome in each trial while electroencephalographic (EEG) was recorded. The feedback-related negativity (FRN) elicited by the positive alternative outcome was larger than that elicited by the negative alternative outcome, suggesting that the participants evaluated the positive alternative outcome as negative feedback. Moreover, the FRN and the P3 elicited by the chosen outcome were influenced by the valence of the alternative outcome. The current study reveals that the alternative outcome is treated as important information even though it is economically neutral.